2015
DOI: 10.1002/jbmr.2753
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulated miR-98 Contributes to Extracellular Matrix Degradation by Targeting IL-6/STAT3 Signaling Pathway in Human Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IDD) is associated with dysregulated expression of microRNAs (miRNAs). However, the precise molecular mechanisms underlying this disorder remain unclear. Therefore, we tested the hypothesis that miRNAs modulate IDD through effects on the IL-6/STAT3 signaling pathway, a potential regulator of IDD. The miRNA expression profile was determined in nucleus pulposus (NP) tissues from patients with IDD and controls, employing miRNA microarray and quantitative real-time PCR (RTqPCR). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 40 publications
3
58
1
1
Order By: Relevance
“…Recently, many studies have reported that different miRNAs regulate NPC apoptosis through their targets in the degenerated IVD. Pro-apoptotic miRNAs include miR-494, miR-138, miR-27a and miR-15a [5,[23][24][25], and anti-apoptotic miRNAs include miR-98, miR-155 and miR-125a [26][27][28]. However, little is known about which miRNAs are associated with TNF-a induced NPC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported that different miRNAs regulate NPC apoptosis through their targets in the degenerated IVD. Pro-apoptotic miRNAs include miR-494, miR-138, miR-27a and miR-15a [5,[23][24][25], and anti-apoptotic miRNAs include miR-98, miR-155 and miR-125a [26][27][28]. However, little is known about which miRNAs are associated with TNF-a induced NPC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this miRNA represses Smad3 resulting in the inhibition in cancer metastasis [160]. Furthermore, miR-98 is highly expressed in OA chondrocytes but has no confirmed target; however, it is an important regulator in intervertebral disc degeneration, where it targets IL-6 [161]. Several miRNAs that are downregulated in OA samples also have unidentified roles in chondrocyte homeostasis.…”
Section: Mirnas Altered In Oa Cartilage Samples But With Unknown Tarmentioning
confidence: 99%
“…Although the molecular mechanisms underlying IDD are not fully understood, it is well established that apoptosis, ECM degradation, cell proliferation, and the inflammatory response contribute to IDD development [7, 8]. Some miRNAs that regulate these processes have been linked to IDD [16, 34, 35]. For example, miR-27b causes the loss of type II collagen by directly targeting MMP13, leading to IDD development [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-27b causes the loss of type II collagen by directly targeting MMP13, leading to IDD development [36]. MiR-146a suppresses IL-1β-induced MMP-13, ADAMTS4, and ADAMTS-5 expression in NP cells [34], and miR-98 downregulation contributes to the loss of type II collagen in IDD [35]. In this study, we found that miR-494 overexpression increased the levels of MMP3, MMP13, ADAMTS4, and ADAMTS5 and decreased that of type II collagen, aggrecan and sGAG; these effects were reversed by inhibiting miR-494.…”
Section: Discussionmentioning
confidence: 99%